Mouse Liver Sinusoidal Endothelium Eliminates HIV-Like Particles from Blood at a Rate of 100 Million per Minute by a Second-Order Kinetic Process - Mates, Jessica M.; Yao, Zhili; Cheplowitz, Alana M.; Suer, Ozan; Phillips, Gary S.; Kwiek, Jesse J.; Rajaram, Murugesan V. S.; Kim, Jonghan; Robinson, John M.; Ganesan, Latha P.; Anderson, Clark L. (Frontiers in Immunology, 2017)
ABSTRACT: We crafted HIV-like particles of diameter about 140 nm that expressed two major HIV-1 proteins, namely, env and gag gene products, and used this reagent to simulate the rate of decay of HIV from the blood stream of BALB/c male mice. We found that most ( 90%) of the particles were eliminated (cleared) from the blood by the liver sinusoidal endothelial cells (LSEC), the remainder from Kupffer cells; suggesting that LSEC are the major liver scavengers for HIV clearance from blood. Decay was rapid with kinetics suggesting second order with respect to particles, which infers dimerization of a putative receptor on LSEC. The number of HIV-like particles required for saturating the clearance mechanism was approximated. The capacity for elimination of blood-borne HIV-like particles by the sinusoid was 112 million particles per minute. Assuming the sinusoid endothelial cells were about the size of glass-adherent macrophages, then elimination capacity was more than 540 particles per hour per endothelial cell.